Macrophage Migration Inhibitory Factor Deficiency Augments Doxorubicin‐Induced Cardiomyopathy. Issue 6 (12th December 2013) - Xu, Xihui; Bucala, Richard; Ren, Jun
Abstract : Background: Recent evidence has depicted a role of macrophage migration inhibitory factor (MIF) in cardiac homeostasis under pathological conditions. This study was designed to evaluate the role of MIF in doxorubicin‐induced cardiomyopathy and the underlying mechanism involved with a focus on autophagy. Methods and Results: Wild‐type (WT) and MIF knockout (MIF −/− ) mice were given saline or doxorubicin (20 mg/kg cumulative, i.p.). A cohort of WT and MIF −/− mice was given rapamycin (6 mg/kg, i.p.) with or without bafilomycin A1 (BafA1, 3 μmol/kg per day, i.p.) for 1 week prior to doxorubicin challenge. To consolidate a role for MIF in the maintenance of cardiac homeostasis following doxorubicin challenge, recombinant mouse MIF (rmMIF) was given to MIF −/− mice challenged with or without doxorubicin. Echocardiographic, cardiomyocyte function, and intracellular Ca 2+ handling were evaluated. Autophagy and apoptosis were examined. Mitochondrial morphology and function were examined using transmission electron microscopy, JC‐1 staining, MitoSOX Red fluorescence, and mitochondrial respiration complex assay. DHE staining was used to evaluate reactive oxygen species (ROS) generation. MIF knockout exacerbated doxorubicin‐induced mortality and cardiomyopathy (compromised fractional shortening, cardiomyocyte and mitochondrial function, apoptosis, and ROS generation). These detrimental effects of doxorubicin were accompanied by defective autophagolysosome formation, the effect of which was exacerbated by MIF knockout. Rapamycin pretreatment rescued doxorubicin‐induced cardiomyopathy in WT and MIF −/− mice. Blocking autophagolysosome formation using BafA1 negated the cardioprotective effect of rapamycin and rmMIF. Conclusions: Our data suggest that MIF serves as an indispensable cardioprotective factor against doxorubicin‐induced cardiomyopathy with an underlying mechanism through facilitating autophagolysosome formation.